ACCUMULATION OF DRY MASS, POTASSIUM AND PHOSPHORUS DURING THE DEVELOPMENT CYCLE OF YELLOW VALENCIA MELON FERTILIZED WITH POTASSIUM CHLORIDE AND POTASSIUM SULPHATE (Editora Impacto Científico, 2025)
The aim of this work was to determine the accumulation curves of dry mass and P and K throughout the growth of drip-irrigated Valenciano Amarelo melon trees in Januária, MG, fertilized with potassium sulphate and potassium chloride. The aerial parts were collected when the plants were transplanted and at 9, 15, 22, 29, 37, 45, 55 and 64 days after transplanting (DAT), separating them into vegetative and reproductive structures. Dry mass, P and K accumulation were measured. In both potassium fertilizer sources tested, the plant growth models followed logistic patterns. In those plants fertilized with potassium chloride, the maximum rates of accumulation of DM in the branches - 5.56 - and in the aerial part - 12.01 g - occurred at 44 and 51 DAT, respectively. As for plants fertilized with potassium sulphate, the maximum accumulation rates of 5.05 g of dry mass of branches and 15.64 g of dry mass of aerial part occurred at 48 and 52 DAT. The reproductive structures became present after the 37th DAT in plants fertilized with both potassium chloride and potassium sulphate. The maximum accumulations of 54.28 mg of P and 78.67 mg of K occurred at 46 and 47 DAT in the plants fertilized with potassium chloride. These values were lower than the 65.99 mg of P and 80.35 mg of K that occurred at 50 and 50 DAT respectively when fertilizing with potassium sulphate. These values were 65.99 mg of P and 80.35 mg of K, respectively, at 50 and 50 DAT when fertilizing with potassium sulphate. In general, plant dry mass gains became more significant after the 35th DAT in most of the situations studied. The accumulated amounts per plant at the end of the 64-day cycle were 324.37 and 250.83 g of shoot dry mass; 114.86 and 120.52 g of branch dry mass; 1,671.81 and 1,602.65 mg of K; and 1,426.84 and 1,164.49 mg of P in the growth of melon trees fertilized with potassium sulphate and potassium chloride, respectively. Fertilizing with potassium sulphate, compared to potassium chloride, resulted in plants richer in K and P at the end of the evaluation cycle. The dry mass, K and P accumulation curves indicate that top-dressing fertilizations should begin before the 35th day after transplanting the melon tree so that the nutrient reserves in the soil meet the growth demands in the following months.